Modes Of Atomic Force Microscopy In Investigation Of The Surface Topography Of Nickel-Doped Silicon Solar Cell. (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
This work describes the operating modes of atomic force microscopy (AFM), as well as its application in the study of various impurity silicon. The difference between using AFM in contact and semi-contact mode is shown. It is assumed that the combined use of these two modes in the study of impurity silicon is optimal.